Migration in India: An Overview of Recent Evidence - Chand, Himal (2005)
This paper looks into the dynamics of trends and patterns of internal migration in India and analyses the extent and direction of the migration. Migration for reasons of employment is an important aspect, which has been dealt with in detail to understand the related issues and their implications. The paper is based mainly on the data of the National Sample Survey 55th round, 1999-2000. The results have also been supported by evidence from the census data on migration wherever necessary. Trends in international migration have also been discussed briefly. The analysis indicates that the proportion of internal migrants to the total population has declined over a period. Similar trends are witnessed globally. The share of the migrants in the total population is higher in urban areas than in rural areas. Females migrate more than the males in rural as well as urban areas because most of the female migration is due to marriage. Males from both the rural and urban areas have largely shown no tendency to migrate to the rural areas because most of them migrate for economic reasons. The lack of employment opportunities in the rural areas and better employment prospects and infrastructure amenities in the urban areas motivate males to migrate to urban areas. Short distance migration is predominant. Rural to urban and urban to urban migration is male selective. A comparison of activity status of the migrants before and after migration indicates that the proportion of males as well as females has risen after migration both in rural and urban areas. However, excessive migration to the urban areas has serious consequences for the urban infrastructure, civic amenities, environment etc. Thus, there is an immense need for developing rural and backward regions of the country to have a balanced development and stem disproportionate growth of urban areas.